Advanced physical techniques for gene delivery based on membrane perforation - Xiaofan Du; Jing Wang; Quan Zhou; Luwei Zhang; Sijia Wang; Zhenxi Zhang; Cuiping Yao (Taylor & Francis Group, 2018)
Gene delivery as a promising and valid tool has been used for treating many serious diseases that conventional drug therapies cannot cure. Due to the advancement of physical technology and nanotechnology, advanced physical gene delivery methods such as electroporation, magnetoporation, sonoporation and optoporation have been extensively developed and are receiving increasing attention, which have the advantages of briefness and nontoxicity. This review introduces the technique detail of membrane perforation, with a brief discussion for future development, with special emphasis on nanoparticles mediated optoporation that have developed as an new alternative transfection technique in the last two decades. In particular, the advanced physical approaches development and new technology are highlighted, which intends to stimulate rapid advancement of perforation techniques, develop new delivery strategies and accelerate application of these techniques in clinic.